Age-related differentiations of Th1/Th2 cytokines in newborn infants - Efthimia Protonotariou; Ariadne Malamitsi-Puchner; Demetrios Rizos; Basiliki Papagianni; Evangelia Moira; Angeliki Sarandakou; Demetrios Botsis (Hindawi Limited, 2004)
OBJECTIVE: To evaluate age-related differentiation of immune response in newborns by measuring serum concentrations of interleukin-2 (IL-2), interleukin-4 (IL-4) and interferon-γ (IFN-γ) during the perinatal period.